قضايا ترجمة القرآن الكريم في ضوء دراسة الترجمة الحديثة - Abd. Rahman, Akmal Khuzairy (IIUM Press, International Islamic University Malaysia, 2019)
This book attempts to address the issues surrounding the efforts of translating the Holy Quran with a special attention given to the Malay translations. It deals with the issue of the translatability of the Quran both from the translations studies perspectives and the Islamic point of view with the intention to complement the latter with the modern explanations that would suit better the understanding of our time. It also aims to explain the inimitability of the Holy Quran form a non-Arab point of view that relies on the notion that translation is a mere approximation effort that inevitably will result in the loss, addition or reduction of the original meaning. In some examples it even distorts it to suit the need of its manipulator or translator. The problems of equivalence between the source and the target text is explored through practical examples to demonstrate to the students the practical aspects of the study. Meaning as the focal point in translation is analytically discussed theoretically and practically with ample and demonstrative examples. In conclusion, the book tries to emphasize that translation in general can never substitute the original text therefore due to aspects of inequivalence and loss of meaning in the process of transfer of recreation of the original text. Similarly, the translation of the Holy Quran to any language is not more than an approximation of the original, a shade between the possible shades of the original meanings.